Assessment of The Memory Buffer Size in NGN Networks when Transferring Different Traffic Types - Mammadov, F.H.; Hasanov, M.H.; Garayev, N.Ch. (Herald of Azerbaijan Engineering Academy, 2023)
The matters are considered related to Poisson distribution- based voice transferred using IP packets, as well related to the assessment of the memory buffer size in NGN networks when transferring selfsimilar traffics. In order to assess the memory buffer size in these networks, the approaches are proposed based on Poisson distribution- based voice, as well corresponding one- channel classic mass service systems of M/M/1 and M/D/1 types reflecting exponential and deterministic distribution laws of the service time of self- similar traffics.